1970
DOI: 10.5424/sjar/20110903-423-10
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and pollen effect on the transmission of the chemical components of the almond kernel

Abstract: The chemical components of the almond kernel are traits contributing to almond quality and must be considered in breeding programs searching for high-quality almonds. Thus, total protein, oil content, fatty acid composition and tocopherol content were determined in 200 genotypes from four progenies from the almond (Prunus amygdalus Batsch) breeding program of Centro de Investigación y Tecnología Agroalimentaria de Aragón (CITA), Spain. All components showed significant differences among genotypes, as well also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
4
18
0
Order By: Relevance
“…Oil content in almond kernel shows a high heritability value of 57% (Font i Forcada et al, 2011), confirming that the genetic Table 1. Oil and fatty acid composition of the kernels of 73 almond cultivars of different geographical origin for 2 crop years.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…Oil content in almond kernel shows a high heritability value of 57% (Font i Forcada et al, 2011), confirming that the genetic Table 1. Oil and fatty acid composition of the kernels of 73 almond cultivars of different geographical origin for 2 crop years.…”
Section: Resultssupporting
confidence: 59%
“…All variables were jointly examined and their correlation coefficients are shown in Table 3. No correlations were found between oil content and the percentage of the main fatty acids in both years of study with the only exception of a significant positive correlation between the contents of oil and of palmitic acid in 2008, although previous studies reported that oleic acid is positively correlated with oil content (Font i Forcada et al, 2011;Kodad and Socias i Company, 2008). A high negative correlation was found between palmitic and both the oleic acid and the O/L ratio (Table 3).…”
Section: Countrymentioning
confidence: 74%
See 2 more Smart Citations
“…The study of the almond cross ‘Vivot’ × ‘Blanquerna’ (V × B) has allowed a linkage map of this progeny to be constructed [29], and the chemical composition of the kernels of its plants to be determined [22]. Thus, our objective was to identify QTL associated with the different chemical components of the almond kernel and thus establish a genetic tool to be applied in an almond breeding program aiming at increased kernel quality.…”
Section: Introductionmentioning
confidence: 99%